Impact of Land Use Changes on Irrigation Systems and Water Balance in the Cimanuk River Basin - Ariyani, Dwi; Trisno Lestari, Rini; Prautama Dewi, Atri; Yasmin Kanwar, Sonia; Putri Kirani, Fachriza (Fakultas Teknik, Universitas Brawijaya, 2024)
Water resources are crucial for life and the economy, especially in the Cimanuk River Basin, where irrigation supports agricultural productivity. Population and economic growth have led to significant changes in land use that impact irrigation systems. The shift from agricultural to non-agricultural land, along with factors such as urbanization, flooding, drought, and pests, has reduced the area of farmland and decreased rice productivity in West Java. This study aims to analyze changes in land use and their effects on the irrigation system in the Cimanuk River Basin. The research methods include analyzing combined data such as remote sensing, statistical tests, evapotranspiration calculations, and irrigation water needs to assess the water balance of irrigation based on water availability and demand. The findings reveal a significant decrease in agricultural land coverage, from 37.48% of the total area of the Cimanuk River Basin in 2000 to 22.79% in 2023. This change in land cover affects irrigation needs and impacts the water balance in the Cimanuk River Basin, resulting in a water deficit between availability and irrigation needs. The water deficit occurs during peak dry months, such as July, with a maximum deficit of 215.72 m³/second, indicating that the water requirements for irrigation are often not met optimally.